Regional Integration and Economic Security: Evaluating Kenya’s Experience under the EAC Framework (National Security: A Journal of the National Defence University-Kenya, 2025)
This study investigates the impact of East African Community (EAC) integration on Kenya’s economic security by evaluating the outcomes of the Customs Union, Common Market, and proposed Monetary Union. Utilising a mixed-methods design that integrates survey data (n = 170), semi-structured interviews (n = 15), and macroeconomic indicators (2010–2024), the study develops a composite Economic Security Index (ESI) encompassing trade efficiency, labour mobility, and fiscal health. Findings show that Kenya’s ESI improved from 52.1 in 2010 to 68.4 in 2023, with the Common Market—especially labour mobility—emerging as the strongest driver (β = 0.402). However, progress remains uneven: the manufacturing and logistics sectors benefited from adherence to the Common External Tariff, while agriculture lagged due to persistent non-tariff barriers (NTBs) and phytosanitary disputes. Monetary integration showed the weakest impact, constrained by inflation divergence and fiscal asymmetries among member states. The study extends Balassa’s (1961) integration model by revealing asymmetric policy spillovers and the critical role of institutional enforcement. Qualitative data expose regulatory fragmentation, informal payments at borders, and licensing delays that hinder professional mobility. Policy recommendations include digitising customs via blockchain, establishing mutual recognition agreements, and capitalising a regional small and medium enterprises credit guarantee fund. These insights offer a nuanced understanding of regional integration’s potential and limitations in advancing economic security in Africa.
Keywords: Regional Integration, Economic Security, Kenya, Customs Union